Disfuncionalidad familiar y rendimiento académico de estudiantes de la Unidad Educativa “San Vicente de Paúl”, parroquia Changaimina, Provincia de Loja, periodo 2024-2025 - Martha Esperanza, Jiménez Jiménez (2024)
The present study analyzed how family dysfunction influences the academic performance of students at the “Unidad Educativa San Vicente de Paúl”, through the development of specific objectives such as the theoretical foundation, the situational diagnosis and the development of a proposal; all this through an exploratory design with a mixed approach methodology, combining the application of surveys to a non-probabilistic intentional sample of parents and a semi-structured interview with a teacher. The results revealed that family dysfunction has a negative influence on students' school performance, with factors such as: absence of effective dialogue, constant conflicts and absence of emotional support were identified as main contributors to an environment of stress and instability that affects students' ability to focus and actively participate in their lessons; in addition, it was found that students from dysfunctional families presented lower academic performance compared to those from functional families. In response to these findings, several intervention strategies were proposed, such as the implementation of psychological and emotional support programs for students, and educational workshops for parents focused on optimizing communication and conflict resolution. These strategies attempt to improve collaboration between the educational institution and families, creating a healthier environment conducive to learning. In conclusion, family dysfunction negatively affects student performance, the findings of which underscore the importance of interventions at both the educational and family levels to reduce these effects through support and awareness strategies that improve school performance and the emotional well-being of students affected by family dysfunctionality.